Answer:
![f(x)=2(2)^(0.5x)-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/j2gqqgr8au3fw5tq04lgrzzcuq5xyxjeu3.png)
Explanation:
Parent function:
![g(x)=2^x](https://img.qammunity.org/2023/formulas/mathematics/high-school/x6one7f2k74j3nwgjnmo7tqyixmfl7hvgk.png)
Properties of the given parent function:
- y-intercept at (0, 1)
- horizontal asymptote at y = 0
- As x → -∞, y → 0
- As x → ∞, y → ∞
Given form of function f(x):
![f(x)=a(b)^(kx)+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/nysn2wm3gfhsjfx178v7tw5dlpd0dt80f6.png)
If the parent function is
then b = 2:
![\implies f(x)=a(2)^(kx)+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/tppwpva0zuq846072mebfoel86ajyk3mps.png)
From inspection of the graphed function f(x):
- y-intercept at (0, -1)
- horizontal asymptote at y = -3
Therefore, the y-intercept has shifted 2 units down, yet the asymptote has shifted 3 units down. This implies that there has been a vertical shift of 3 units down and a vertical stretch.
The vertical shift is denoted by the variable "c" so c = -3:
![\implies f(x)=a(2)^(kx)-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/zs7wwemd0f3fye18ucqb41mtrjpl0cdpcq.png)
The vertical stretch is denoted by the variable "a". To find value of a, substitute the point of the y-intercept into the equation:
![\begin{aligned}f(0) & = -1\\\implies a(2)^(k * 0)-3 & =-1\\a-3 & = -1\\a-3+3 & = -1+3\\a & = 2\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/wf3f1niky92rs51x8ni2c8rra4yaaicy5j.png)
Therefore, as a = 2:
![\implies f(x)=2(2)^(kx)-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/sag1astm8debtilztdw78bw6l3jipohcwu.png)
From inspection of the given graph, the curve passes through point (4, 5). Substitute this point into the equation to find the value of k:
![\begin{aligned}f(4) & = 5\\\implies 2(2)^(4k)-3 & =5\\2(2)^(4k)& =8\\(2)^(4k)& =4\\(2)^(4k)& =2^2\\4k & = 2\\k & = 0.5\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ce1si4coiv7lynwf3bgzo73iu5591uyo0k.png)
Therefore, the equation of the function f(x) is:
![\implies f(x)=2(2)^(0.5x)-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/ivxlngd44vswhkpzd4o7ctk1a2538axw9v.png)